2010
DOI: 10.1186/1471-2180-10-172
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced IL-8 activation in human intestinal epithelial cells is accompanied by specific histone H3 acetylation and methylation changes

Abstract: BackgroundThe release of LPS by bacteria stimulates both immune and specific epithelial cell types to release inflammatory mediators. It is known that LPS induces the release of IL-8 by intestinal mucosal cells. Because it is now emerging that bacteria may induce alteration of epigenetic patterns in host cells, we have investigated whether LPS-induced IL-8 activation in human intestinal epithelial cells involves changes of histone modifications and/or DNA methylation at IL-8 gene regulatory region.ResultsRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 26 publications
10
73
0
Order By: Relevance
“…The change in gDNA methylation level found in this study was due to microbial infection and this is evident from previous studies which described the effect of lipopolysaccharide on DNA methylation [8][9][10].…”
Section: Discussionsupporting
confidence: 79%
“…The change in gDNA methylation level found in this study was due to microbial infection and this is evident from previous studies which described the effect of lipopolysaccharide on DNA methylation [8][9][10].…”
Section: Discussionsupporting
confidence: 79%
“…29 LPS-induced IL-8 activation in human intestinal epithelial cells was also reported to be accompanied by changes of specific histone H3 acetylation and methylation. 30 Histone deacetylation is mainly regulated by HDACs that control gene expression by means of removing acetyl groups from lysine residues in histone molecules and is closely related to epigenetic regulation of different genes. In our previous study, we demonstrated that LPS challenge causes deacetylation of H3 and H4 and inhibition of Thy-1 gene transcription in cultured mouse lung fibroblasts, indicating that LPS may silence Thy-1 gene through histone deacetylation at the Thy-1 gene promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study indicated that a change in H3S10 phosphorylation status at IL-6 gene promoter is related to Hp infection through NFkB/ERK/p38 pathway [26]. We have recently demonstrated that chromatin and DNA methylation modifications accompany Hp-induced Cox-2 activation in gastric epithelial cells [27] and LPS-induced IL-8 activation in human intestinal epithelial cells [28]. In this work, we hypothesized that Hp infection may have a direct impact on epigenetic status of iNOS gene in gastric cells and that the Hp-induced iNOS activation may be mediated by histone modifications at iNOS gene regulatory regions.…”
Section: Introductionmentioning
confidence: 95%